Effects of dihydrotestosterone on osteoblast activity in curdlan-administered SKG mice and osteoprogenitor cells in patients with ankylosing spondylitis - Jo, Sungsin (Arthritis Res Ther, 2020)
BACKGROUND: Ankylosing spondylitis (AS) is characteristically male-predominant, and progressive spinal ankylosis affects male patients more severely; however, the hormonal effects in males with AS are poorly understood. METHODS: In the present study, the regulatory effects of dutasteride, a 5-α reductase inhibitor that blocks the conversion of testosterone to dihydrotestosterone (DHT), were examined in curdlan-administered male SKG mice to determine spinal bone formation, bone metabolism-related markers, and interleukin (IL)-17A cytokine and T cell populations. In addition, the effects of DHT on primary osteoprogenitors from the facet joints of AS patients were assessed based on osteoblast-related parameters. DHT level was measured, and the correlation with modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) was analyzed in AS patients. RESULTS: In curdlan-administered SKG mice, dutasteride treatment resulted in an increased accumulation of hydroxyapatite in the spine which was positively correlated with serum IL-17A levels. In the analysis of bone metabolism-related molecules, a decrease in sclerostin levels was observed in the sera in the dutasteride group. Continuous exposure to DHT resulted in fewer calcium deposits in AS osteoprogenitors during osteoblast differentiation. DHT-treated AS osteoprogenitors showed decreased osteocalcin and increased DKK1 and SOST1 mRNA expression, supporting the results of the in vivo experiments. Treatment with dutasteride upregulated bone formation in the spine of curdlan-administered SKG mice and DHT treatment downregulated osteoblast differentiation in vitro. CONCLUSIONS: Treatment with dutasteride affected the bone formation in the spine of curdlan-treated SKG mice, and DHT treatment attenuated osteoblast differentiation in vitro. Therefore, contrary to what could be expected if osteoblasts contributed to spinal ankylosis, DHT inhibition might increase rather than decrease the progression of spinal ankylosis despite the higher levels of DHT observed in many AS patients.